Structure and properties of the catalytic site of nitric oxide reductase at ambient temperature - Daskalakis, Vangelis; Ohta, Takehiro; Kitagawa, Teizo; Varotsis, Constantinos (My University, 2015)
Nitric oxide reductase (Nor) is the third of the four enzymes of bacterial denitrification responsible for the catalytic formation of laughing gas (N2O). Here we report the detection of the hyponitrite (HO-N = N-O-) species (νN-N = 1332 cm- 1) in the heme b3 Fe-FeB dinuclear center of Nor from Paracoccus denitrificans. We have also applied density functional theory (DFT) to characterize the bimetallic-bridging hyponitrite species in the reduction of NO to N2O by Nor and compare the present results with those recently reported for the N-N bond formation in the ba3 and caa3 oxidoreductases from Thermus thermophilus.
Keywords: Density functional theory; Heme proteins; Hyponitrite; Oxidoreductases; UV Raman spectroscopy